The Use of Digital Educational Games as Learning Media: A Study on Elementary School Teachers - I Putu Andika Satyana Putra; Made Vina Arie Paramita (International Journal of Elementary Education, 2023)
Educational games are one of the learning media that can help the student learning process, especially in the digital era as it is today. This study analyzes elementary school teachers' use of digital educational games as learning media. This research is descriptive research with a survey method. The population in this study is 4315 elementary school teachers. Sampling was carried out using cluster sampling and random sampling techniques so that the number of samples in this study was 98 teachers. The research data were collected using a questionnaire, which was then analyzed descriptively. Based on the research that has been done, the results show that school teachers use digital educational games quite often as learning media: 52 teachers (53.06%) of a total of 98 samples are in the sufficient category. The most widely used digital educational game application is Quizziz. The main reason for using digital educational games is that digital educational games can improve students' cognitive abilities. The main advantage of using educational games as a learning medium is making the learning process more efficient. The main obstacles experienced were related to the internet, which did not support it, and digital educational game applications, which often experienced errors. Hence, they had to start over from the beginning. It was concluded that elementary school teachers often used digital educational games as learning media.